(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The purpose of this research was to reconstruct from the perspective of social history and through documentary review and interpretation and indepth interviews, the artisticcultural dynamics of the Danza Nacionalista in Venezuela, as an expression of folklore and popular culture in the period 19482015. In its origins, the Danza Nacionalista promoted from the Retablo de Maravillas, led by the writer Manuel Rodríguez Cárdenas, was part of a political project to promote a sense of nation among the inhabitants of a country that, despite its mining wealth, was disintegrated since its creation as a republic in the first third of the 19th century. We address the historical passing of dance and some conceptual details about dance, popular culture, folklore and nation. Seen in time, it is worth affirming that the Danza Nacionalista, which later acquired the denomination of Danzas Venezuela, earned its space in the artistic endeavor and in the popular imagination of the country, an imaginary rooted in the figure of Yolanda Moreno, the “bailarina del pueblo venezolano".